2023
DOI: 10.3389/fmicb.2023.1278886
|View full text |Cite
|
Sign up to set email alerts
|

Metal tolerance and biosorption capacities of bacterial strains isolated from an urban watershed

Grace Pagnucco,
Dustin Overfield,
Yanesa Chamlee
et al.

Abstract: Rapid industrialization and urbanization have led to widespread metal contamination in aquatic ecosystems. This study explores the metal tolerance and biosorption characteristics of four bacterial strains (Serratia sp. L2, Raoultella sp. L30, Klebsiella sp. R3, and Klebsiella sp. R19) isolated from Saint Clair River sediments. These strains effectively removed various metal cations (As3+, Pb2+, Cu2+, Mn2+, Zn2+, Cd2+, Cr6+, and Ni2+) in single and multi-metal solutions. Minimum inhibitory concentration (MIC) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Microbial biosorption has gained prominence as an environmentally friendly method for extracting heavy metals from water (Bowman et al, 2018;Tiquia-Arashiro, 2018, Pagnucco et al, 2023. This process involves a variety of interactions between microbial cell surfaces and metal ions, including physical adsorption, ion exchange, complexation, and surface precipitation (Tiquia-Arashiro, 2018;Tiquia-Arashiro and Pant, 2019;Pagnucco et al, 2023). FT-IR spectroscopy allows researchers to investigate the molecular-level alterations on microbial cell surfaces during metal binding.…”
Section: Microbial Biosorption Studies With Metalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microbial biosorption has gained prominence as an environmentally friendly method for extracting heavy metals from water (Bowman et al, 2018;Tiquia-Arashiro, 2018, Pagnucco et al, 2023. This process involves a variety of interactions between microbial cell surfaces and metal ions, including physical adsorption, ion exchange, complexation, and surface precipitation (Tiquia-Arashiro, 2018;Tiquia-Arashiro and Pant, 2019;Pagnucco et al, 2023). FT-IR spectroscopy allows researchers to investigate the molecular-level alterations on microbial cell surfaces during metal binding.…”
Section: Microbial Biosorption Studies With Metalsmentioning
confidence: 99%
“…These modifications provide valuable information about the specific functional groups responsible for metal absorption and the ensuing chemical reactions on the microbial cell surface. Comprehensive analysis of biosorption of metal ions using FT-IR have been studied in bacteria (Pardo et al, 2003;Oh et al, 2009;Gutiérrez-Corona et al, 2016;Dhanwal et al, 2018;Saranya et al, 2018;Pagnucco et al, 2023), algae (Michalak et al, 2013;Gu and Lan, 2021) and fungi (George et al, 2012;Gutiérrez-Corona et al, 2016;Sundararaju et al, 2022;Table 9).…”
Section: Microbial Biosorption Studies With Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some bacterial cells on Sr-TCP coating also showed cracks and alterations in their rod-shape ( E. coli ) and spherical ( S. aureus ) morphology. Changes in the cell morphology may be either a consequence of the disruption and loss of functionality of the bacterial cells or an attempt of the bacterial cells to tolerate the toxicity of the metal present on the surface by modifying its cellular structure ( Mathivanan et al, 2021 ; Pagnucco et al, 2023 ). Based on what is known for other toxic metals, strontium might also inhibit the expression of genes involved in bacterial cell wall formation and production of septal peptidoglycan during cell division with possible effects on cellular morphology ( Ahmed et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…FTIR spectroscopy is a powerful tool for monitoring and revealing microorganism composition and responses to the environment. So, it was performed to confirm the interactions between metal ions and functional groups on the surface of the microbial cells in comparison to untreated ones (Dhanwal et al,2018;Rizvi and Saghir-Khan 2019;Pagnucco et al,2023 and. Where, Dhanwal et al,(2018) identified the surface chemical functional groups of the metal tolerant strain, Bacillus cereus FIT10, by FTIR spectroscopy as hydroxyl, carboxyl, amine, and halide, which might be involved in the biosorption of heavy metals, lead, chromium, copper, and nickel.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 99%